2013
DOI: 10.3390/ijerph10030830
|View full text |Cite
|
Sign up to set email alerts
|

Potential Changes in Rat Spermatogenesis and Sperm Parameters after Inhalation of Boswellia papyrifera and Boswellia carterii Incense

Abstract: In this study the effect of Boswellia papyrifera (B. papyrifera) and Boswellia carterii (B. carterii) smoke exposure on spermatogenesis and sperm parameters in male albino rats was investigated. Rats (n = 11) were exposed daily in smoking chambers to smoke emanated by burning 4 g each of either B. papyrifera or B. carterii for 48 days. At the end of exposure duration rats were killed, and the testes were excised and analysed for histopathological and ultrastructural changes. Sperm analysis including total sper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 16 publications
1
19
0
Order By: Relevance
“…3,4 Numerous toxicological and epidemiological studies have shown that PM 2.5 is connected with increased risk of cardiopulmonary disorders, obesity, diabetes mellitus, and even disadvantageous birth outcomes. [5][6][7][8] Recently, toxicological research have noted that PM 2.5 exposure could affect the process of spermatogenesis, 9,10 thus cause the reductions of sperm quality and quantity. 10,11 Study of Radwan et al showed that PM exposure could decrease the level of testosterone in human.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 Numerous toxicological and epidemiological studies have shown that PM 2.5 is connected with increased risk of cardiopulmonary disorders, obesity, diabetes mellitus, and even disadvantageous birth outcomes. [5][6][7][8] Recently, toxicological research have noted that PM 2.5 exposure could affect the process of spermatogenesis, 9,10 thus cause the reductions of sperm quality and quantity. 10,11 Study of Radwan et al showed that PM exposure could decrease the level of testosterone in human.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously shown that long term Arabian incense smoke exposure contributes to increased oxidative stress and inflammation in lung, liver and heart tissues of rats (Al-Attas et al, 2015;Hussain et al, 2014). We have also found that incense smoke exposure results in insulin resistance, dyslipidemia, altered spermatogenesis and sperm parameters in male Wister rats (Ahmed et al, 2013;Alokail et al, 2011). Considering the high susceptibility nature of kidney to oxidative stress, we suspected that chronic exposure to incense smoke may have deleterious effects on kidney functions and architecture.…”
Section: Introductionmentioning
confidence: 82%
“…Considering the high susceptibility nature of kidney to oxidative stress, we suspected that chronic exposure to incense smoke may have deleterious effects on kidney functions and architecture. To test this possibility we exposed male albino rats to bakhour or oudh, the two commonly used well characterized types of incense used in Middle Eastern region (Ahmed et al, 2013;Al-Attas et al, 2015;Alokail et al, 2011;Al-Rawas et al, 2009;Dalibalta et al, 2015;Hussain et al, 2014;Yeatts et al, 2012), for extended durations and measured the kidney functional markers and tissue ultrastructural changes. Further, we examined the oxidative stress, inflammation and the genetic expression of xenobiotic metabolizing enzymes including CYP1A1 and CYP1A2 in kidney tissue to understand the possible underlying mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…Here, serum testosterone level was decreased but testicular cholesterol level increased in CPA‐treated rat as cholesterol is the main precursor of the male androgens (Turcu et al, ). Seminal vesicular fructose level was elevated in CPA‐treated condition may be due to the decreased fructose metabolic enzymes activities that lead to unavailability of fructose to spermatozoon for using as bio‐fuel, resulted in diminution of the sperm count, motility and viability (Ahmed, Al‐Daghri, Alokail, & Hussain, ). Accessory sex organs weight lessened in CPA‐treated rat as testosterone level decreased significantly (Al‐Harbi, Hadi, & Abbas, ).…”
Section: Discussionmentioning
confidence: 99%